Experiment and finite element analysis of bending behavior of high strength steel-UHPC composite beams. (1st September 2022) - Tong, Lewei; Chen, Luhua; Wang, Xiaoqing; Zhu, Jia; Shao, Xiaodong; Zhao, Zheng
Highlights: Flexural experiments were conducted on composite beam specimens between high-strength steel with nominal yield strength of 690 MPa and ultra-high-performance concrete (UHPC) with cubic compressive strength of 140 MPa. The effects of the degree of shear connection and layouts of the studs on flexural performance of high-strength steel—UHPC composite beam were investigated. Finite element analysis was conducted to compare the influence on flexural performance of composite beam between UHPC and normal concrete. Abstract: High-strength structural steel (HSS) and ultra-high-performance concrete (UHPC) are materials countries hope to use in civil engineering construction. This study investigated the static bending performance of HSS-UHPC composite beams through experiment and finite element analysis. First, four static bending tests were conducted. The test parameters included the degree of shear connection and the arrangement of studs (single-stud and group-stud arrangement). The group-stud arrangement was applicable for the assembly construction, which developed increasing fast in civil engineering. The experimental results showed that the failure mode of the composite beam with partial shear connection was stud fracture caused by an insufficient number of studs to withstand the shear force on the steel–concrete interface; for the composite beam with full shear connection, the failure mode was the crushing of the UHPC slab at the loading point. The deflections at mid-span for both the single-stud and group-stud specimens were the same in the elastic stage. However, the deflection of the group-stud specimen was greater than that of the single-stud specimen in the plastic stage. The results showed that the bending stiffness of the composite beam with studs arranged in a group decreased faster. Under the same load, the steel–concrete interfacial slip of the group-stud specimen was also greater than that of the single-stud specimen. Finally, this study compared the mechanical properties of the Q690-UHPC and Q690-normal strength concrete C60 (NSC60) composite beams through finite element analysis. It was found that under the same deflection, the damage of the normal strength concrete slab was more substantial than that of the UHPC slab. The bending stiffness and ultimate bending capacity of the Q690-UHPC composite beam were greater. Q690 HSS had better material strength matching with UHPC than that of normal strength concrete C60.